2019
DOI: 10.1111/ijfs.14182
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritis‐alleviating effects in papain‐induced model rats of chicken cartilage hydrolysate and its peptide fractions

Abstract: This study aims to discover natural bioactive substances as alternative therapies to current medical and surgical treatments for osteoarthritis (OA). Chicken cartilage hydrolysate (CCH) was produced using trypsin and separated via ultrafiltration into CCH-I (molecular weight (MW) > 10 kDa) and CCH-II (MW <10 kDa). Results showed that CCH and its fractions (CCH-I and CCH-II) could relieve OA with different extents, and the outcome using these treatments depended on their especial composition. CCH-II (a fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
(28 reference statements)
0
5
0
Order By: Relevance
“… Rabbits Lee et al [ 137 ] Pilose antler ( Cervus elaphus Linnaeus) peptide Deer antlers In vitro , 1–128 μM, 24 h Over-expression of inflammatory factors was inhibited Nucleus pulposus of the vertebra disc Dong et al [ 138 ] Chicken cartilage hydrolysate (Mw < 10 kDa) Chicken Oral, 100 mg/kg/day, 30 days IL-1β, IL-10, TNF-α and MMP-13 levels decreased. Rats Yang et al [ 139 ] Antarctic Krill peptides Antarctic Krill Oral, 195–600 mg/kg/day, 8 weeks Cartilage thickness and area increased. Rats Wang et al [ 140 ] Lunasin Soybean In vitro , 50 and 100 μM, 48 h MMP-3 and MMP-13 decreased.…”
Section: Fdps In the Management Of Ramentioning
confidence: 99%
“… Rabbits Lee et al [ 137 ] Pilose antler ( Cervus elaphus Linnaeus) peptide Deer antlers In vitro , 1–128 μM, 24 h Over-expression of inflammatory factors was inhibited Nucleus pulposus of the vertebra disc Dong et al [ 138 ] Chicken cartilage hydrolysate (Mw < 10 kDa) Chicken Oral, 100 mg/kg/day, 30 days IL-1β, IL-10, TNF-α and MMP-13 levels decreased. Rats Yang et al [ 139 ] Antarctic Krill peptides Antarctic Krill Oral, 195–600 mg/kg/day, 8 weeks Cartilage thickness and area increased. Rats Wang et al [ 140 ] Lunasin Soybean In vitro , 50 and 100 μM, 48 h MMP-3 and MMP-13 decreased.…”
Section: Fdps In the Management Of Ramentioning
confidence: 99%
“…The pathogenesis of osteoarthritis involves the activation of the inflammatory cascade through the stimulation of various cytokines such as TNF-α, IL-10, IL-8, and IL-1β. The study found that the hydrolysis of trypsin in chicken cartilage resulted in a reduction of these cytokine in papain-induced model rats, leading to an alleviation of osteoarthritis symptoms ( 152 ). The silkworm pupa ( Bombyx mori ) protein is rich in valuable peptides.…”
Section: Immunomodulatory Activity Of Bioactive Peptidesmentioning
confidence: 99%
“…In this study, it was seen that CHP1 using 0.25% bromelain and 0.75% papain had the strongest antioxidant activity when compared with other samples. Yang et al (2019) reported that chicken cartilage hydrolysate, fractions >10 kDa, and <10 kDa using trypsin for 3 hours had IC 50 values of 9.80, 18.91, and 7.35 mg/ml, while Alahyaribeik et al (2021) reported that the <3 and <10 kDa fractions from chicken feather hydrolysate using fermented by Bacillus licheniformis had IC 50 values of 5.03 and 6.64 mg/ml, respectively. This showed that chicken head protein hydrolysate had antioxidant activity that was equivalent or even better than chicken cartilage and feather hydrolysate.…”
Section: Ic 50 Dpph Of Chicken Head Protein Hydrolysatementioning
confidence: 99%
“…Antioxidant peptides can come from vegetable proteins such as legumes, or from animal proteins from muscle tissue, milk, egg, and by-products. Bioactive peptides derived from poultry by-products, such as chicken skin (Onuh et al, 2014), chicken cartilage (Yang et al, 2019), chicken blood (Hamzeh et al, 2019) and chicken feathers (Alahyaribeik et al, 2021) showed the ability and potential as antioxidant. Bioactive peptides have good electron donor ability and hydrophobic character, so they can act as antioxidants by donating electrons to free radicals and converting them into stable compounds (Najafian and Babji, 2014).…”
Section: Introductionmentioning
confidence: 99%